Aluminum-plastic co-extruded composite profile with excellent thermal break performance and deformation resistance

KR103020657B1Active Publication Date: 2026-09-16SHIN CHANG IND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250133906
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2026-09-16
Estimated Expiration
2045-09-17

Smart Images

  • Figure 112025106850270-PAT00004_ABST
    Figure 112025106850270-PAT00004_ABST
Patent Text Reader

Abstract

The present invention relates to a composite profile that significantly improves thermal insulation performance and structural stability by integrating an aluminum profile and a micro-foamed PVC (polyvinyl chloride) resin through a co-extrusion process. To this end, the present invention comprises: an aluminum profile extruded to form a window frame; a powder coating layer formed on the outer surface of the aluminum profile; a hot-melt adhesive layer formed on the powder coating layer; a micro-foamed PVC (polyvinyl chloride) layer formed on the hot-melt adhesive layer and containing independent bubbles inside; and a hard skin layer forming the outermost surface of the micro-foamed PVC layer; and is integrally formed by a co-extrusion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an aluminum-plastic composite profile used for windows, door frames, curtain walls, etc., of buildings, and more specifically, to a composite profile that significantly improves thermal insulation performance and structural stability by integrating an aluminum profile and a micro-foamed PVC (polyvinyl chloride) resin through a co-extrusion process. Background Technology

[0003] As global demands for addressing climate change and conserving energy increase, governments around the world are continuously strengthening energy efficiency standards for buildings. Since a significant portion of energy loss in buildings occurs through windows, the development of high-efficiency insulated window systems has now become a necessity rather than an option.

[0004] Aluminum has been highly regarded as a material for window profiles in modern buildings due to its excellent strength, corrosion resistance, workability, and aesthetic appearance. However, the metal's inherently high thermal conductivity (≈200 W / m·K) causes a "thermal bridge" phenomenon, serving as a primary pathway for external heat to easily transfer into the interior during the summer and indoor heating to the exterior during the winter. This not only increases the heating and cooling load and leads to energy waste, but also causes condensation on the profile surface when there is a large temperature difference between the inside and outside, which can result in damage to finishing materials and the growth of mold.

[0005] To address these issues, methods have been used in which insulating materials such as polyamide are inserted between aluminum profiles and mechanically bonded or attached with adhesives. However, due to the significant difference in thermal expansion coefficients between aluminum and plastic insulation, these methods have caused chronic problems such as deformation, breakage, and delamination as stress concentrates at the interface during the shrinkage and expansion processes caused by repeated temperature changes.

[0006] To address these issues, the inventors of the present invention have proposed, as prior art (Korean Registered Patent No. 1891645), a technology that integrates a metal frame as a core by extruding a synthetic resin material to the outside thereof. The aforementioned prior art had the progressive effect of simplifying the structure and improving constructability by directly combining the metal and the synthetic resin material without a separate intermediate insulation member.

[0007] However, the aforementioned prior art also had challenges that needed to be addressed. First, since the synthetic resin material was extruded in a non-foamed (solid) state, there were limitations in maximizing thermal insulation performance. Second, while the direct extrusion bonding between the metal core and the synthetic resin material was superior to conventional bonding methods, it still failed to completely resolve potential stress issues caused by differences in thermal expansion in harsh environments where extreme temperature fluctuations are repeated over long periods. Third, due to the shrinkage of the resin during the extrusion process, it was difficult to achieve complete adhesion with the metal surface, which could result in minute gaps.

[0008] Therefore, there is a need for a more advanced technology that can secure long-term stability by fundamentally strengthening the bonding durability between dissimilar materials while inheriting the advantages of prior art and elevating thermal insulation performance to a higher level. Prior art literature

[0010] Republic of Korea Registered Patent No. 1891645 (Registered on August 20, 2018) The problem to be solved

[0011] The present invention was created to solve the above-mentioned problems, and the objective of the present invention is to provide an aluminum-plastic co-extrusion composite profile that is based on the prior art metal-synthetic resin integrated extrusion technology, maximizes thermal insulation performance, and dramatically improves interfacial bonding strength between dissimilar materials.

[0012] Another objective of the present invention is to provide an aluminum-plastic co-extrusion composite profile that utilizes the natural resin expansion force generated during the extrusion process to ensure that an insulating layer adheres perfectly to the surface of a metal core without any fine gaps, and to implement a multilayer cushioning structure capable of effectively absorbing stress caused by differences in thermal expansion.

[0013] Another objective of the present invention is to provide an aluminum-plastic co-extrusion composite profile that achieves all these functional improvements within a single co-extrusion process without a separate post-processing step, thereby increasing production efficiency and ensuring excellent surface durability against external environments. means of solving the problem

[0015] The present invention for the above purpose relates to an aluminum-plastic co-extrusion composite profile comprising: an aluminum profile extruded to form a window frame; a powder coating layer formed on the outer surface of the aluminum profile; a hot-melt adhesive layer formed on the powder coating layer; a micro-foamed PVC (polyvinyl chloride) layer formed on the hot-melt adhesive layer and containing independent bubbles inside; and a hard skin layer forming the outermost surface of the micro-foamed PVC layer; and is integrally formed by a co-extrusion process.

[0016] In addition, a plurality of dovetail grooves may be machined on the surface of the above aluminum profile where the micro-foamed PVC layer is coated.

[0017] In addition, it is preferable that the microfoamed PVC layer has a thickness of 3 mm to 5 mm.

[0018] And it is preferable that the hard epidermal layer has a thickness of 0.5 mm to 1.0 mm.

[0019] In addition, the powder coating layer can be formed by curing a polyester-based powder paint.

[0020] In addition, it is preferable that the microfoamed PVC layer comprises independent cells with a size of 10 μm to 50 μm. Effects of the invention

[0022] According to the aluminum-plastic co-extrusion composite profile of the present invention, by forming the insulation layer as a micro-foamed PVC layer rather than a non-foamed one, significantly improved insulation performance compared to the prior art is achieved, and also, the expansion pressure generated during foaming strongly adheres the molten resin to the surface of the aluminum profile, thereby achieving perfect integration.

[0023] Furthermore, according to the present invention, by introducing a multilayer interface composed of a powder coating layer and a hot-melt adhesive layer between aluminum and PVC, a significantly higher adhesive strength is secured compared to a simple extrusion bonding method. In particular, the hot-melt adhesive layer with viscoelastic properties effectively absorbs stress caused by differences in thermal expansion, thereby ensuring long-term durability and reliability.

[0024] In addition, according to the present invention, high-speed production is possible through an integrated process in which extrusion and coating are performed simultaneously within a die, resulting in very high productivity. Furthermore, the outermost hard skin layer provides excellent surface hardness and scratch resistance, which has the advantage of improving the durability of the product. Brief explanation of the drawing

[0026] FIG. 1 is a cross-sectional view illustrating an embodiment of the present invention applied to a project window, FIG. 2 is a cross-sectional view illustrating an embodiment of the present invention applied to a sliding window (single-panel type). FIG. 3 is a cross-sectional view illustrating an embodiment of the present invention applied to a sliding window (two-panel type). FIG. 4 is a perspective view illustrating an embodiment of the present invention applied to a curtain wall. Specific details for implementing the invention

[0027] Hereinafter, an aluminum-plastic co-extrusion composite profile according to the present invention will be described in detail with reference to the attached drawings.

[0029] The composite profile according to the present invention has a multilayer structure in which layers performing different functions are organically combined, based on an aluminum profile used as a window frame for construction. The profile has an aluminum profile as a core, and a powder coating layer, a hot-melt adhesive layer, a micro-foamed PVC layer, and a hard skin layer are sequentially laminated on its outer surface. All these layers are perfectly integrated physically and chemically through a single co-extrusion process.

[0030] FIG. 1 is a cross-sectional view illustrating an embodiment of the present invention applied to a project window, FIG. 2 is a cross-sectional view illustrating an embodiment of the present invention applied to a sliding window (single-panel type), FIG. 3 is a cross-sectional view illustrating an embodiment of the present invention applied to a sliding window (two-panel type), and FIG. 4 is a perspective view illustrating an embodiment of the present invention applied to a curtain wall. As shown in the drawings, in the project window, sliding window, and curtain wall, a powder coating layer (2), a heat-melt adhesive layer (3), a micro-foamed PVC layer, and a hard skin layer (5) can be seen laminated on the main aluminum profile (1).

[0031] Each of these components is explained in more detail.

[0032] First, the aluminum profile (1) is a core framework that maintains the structural rigidity and shape of the entire composite profile. In the present invention, it is manufactured by extruding a 6063 alloy, which is commonly used as a window frame material, and serves as a reinforcing material that resists physical loads such as wind pressure or external impact.

[0033] In particular, the aluminum profile (1) according to the present invention is characterized by having a plurality of dovetail grooves (1a) formed on the surface coated with a PVC insulation layer. The dovetail grooves (1a) may be formed as an intaglio structure having a trapezoidal cross-section, but are not limited thereto, and molten PVC resin flows into the grooves during co-extrusion, fills them, and then hardens.

[0034] This structure performs two important functions. First, it physically expands the bonding area compared to a simple flat surface, thereby increasing the bonding strength of the adhesive layer. Second, and more importantly, it exerts a mechanical keying effect in which the cured PVC physically interlocks with the dovetail groove (1a). This provides strong resistance to shear stress caused by differences in thermal expansion coefficients, creating synergy with the chemical bonding strength of the hot-melt adhesive layer (3) to double-suppress delamination. Therefore, the dovetail groove plays a decisive role in ensuring long-term durability and structural integrity.

[0035] The powder coating layer (2) is a multifunctional primer layer that improves durability and adhesion simultaneously by surface modification of the aluminum profile (1). First, the aluminum surface is pretreated through processes such as degreasing, washing, and etching, and then a polyester-based fine powder paint is uniformly applied using an electrostatic spray gun. The powder attached by electrostatic force melts and fuses together in a high-temperature curing furnace (Film Formation) and forms a hard and dense continuous coating film through a cross-linking reaction.

[0036] In addition to the basic protective function of preventing corrosion on exposed aluminum parts where PVC coating is not applied, this film plays a key role in maximizing the chemical bonding strength between the two by transforming the chemically inert aluminum oxide surface into an organic polymer surface with high affinity for hot-melt adhesives.

[0037] The micro-foamed PVC layer (4) is the core component that implements the key thermal insulation performance of the present invention. A supercritical fluid (typically carbon dioxide or nitrogen) is injected into molten PVC resin in a high-temperature, high-pressure state inside an extruder cylinder to create a uniform single-phase solution. As this solution passes through an extrusion die and the pressure drops rapidly, the supersaturated gas forms numerous microbubble nuclei, and these nuclei grow to form a uniform closed-cell structure with a size of 10 to 50 μm.

[0038] This closed-cell structure exhibits excellent thermal insulation performance by suppressing gas convection within the bubbles and minimizing heat conduction. In addition, the present invention actively utilizes the expansion pressure generated as the bubbles grow. This expansion force pushes the molten resin into complex shapes or invisible fine irregularities on the surface of the aluminum profile (1), thereby maximizing the mechanical interlocking effect. This provides a strong physical bonding force in addition to the chemical bonding by the adhesive layer, thereby dramatically improving interfacial stability.

[0039] It is very important that the thickness of this layer be controlled to be between 3 mm and 5 mm. If the thickness is less than 3 mm, it is difficult to satisfy the building energy efficiency standards due to the absolute lack of thickness of the insulation layer. On the other hand, if the thickness exceeds 5 mm, excessive foam expansion pressure may cause the precise position of the aluminum profile (1) to be distorted or deformed during the co-extrusion process, thereby compromising the dimensional stability of the final product. Therefore, a thickness range of 3 to 5 mm is the optimal condition for achieving both the best insulation performance and a stable production process.

[0040] The hot-melt adhesive layer (3) acts as a bridge connecting the powder coating layer (2) (metal-based) and the micro-foamed PVC layer (4) (polymer-based), which have distinctly different physical properties. In particular, the key function is a buffer that relieves stress caused by the large difference in thermal expansion coefficients between aluminum and PVC. This adhesive layer has viscoelastic properties, so when shear stress is applied to the interface due to temperature changes, it does not break but deforms slightly, thereby absorbing and dispersing stress energy.

[0041] Thanks to this stress relief function, interface fatigue failure is suppressed even during thousands or tens of thousands of repeated thermal cycles, ensuring long-term adhesive durability and fundamentally preventing delamination.

[0042] The hard skin layer (5) acts like armor on the outermost part of the composite profile to protect the product from external physical and chemical stress. In the co-extrusion process, the high-temperature molten PVC resin exiting the extrusion die comes into immediate contact with the cooling sizing die. At this time, the resin surface solidifies due to rapid cooling (quenching) without giving time for foam nuclei to grow, forming a high-density, hard, non-foamed layer.

[0043] The thickness of this hard skin layer (5) is precisely controlled to be between 0.5 mm and 1.0 mm. If the thickness is less than 0.5 mm, it lacks resistance to scratches, impacts, etc. that occur during construction or use, and it is difficult to effectively prevent deterioration and discoloration caused by ultraviolet rays (UV). On the other hand, if the thickness exceeds 1.0 mm, the proportion of non-foamed layers that do not contribute to thermal insulation performance becomes excessively high, which impairs the thermal insulation efficiency of the entire profile and causes unnecessary cost increases.

[0044] And this layer has a high surface hardness of 80 or higher on the Shore D scale, and provides excellent weather resistance and color stability, maintaining the initial appearance even after long-term use.

[0046] Below, to specifically verify the effects of the present invention, performance was compared and evaluated through examples and comparative examples.

[0048] [Example 1]

[0049] To manufacture a composite profile according to the present invention, the surface of a 6063-T5 alloy aluminum profile was first activated through a multi-stage chemical pretreatment process such as degreasing and etching. Subsequently, a polyester-based powder coating was applied using an electrostatic coating method to form a uniform film thickness within the range of 30 to 60 μm, and a hard powder coating layer was completed by curing in a curing oven at 200°C for 10 minutes.

[0050] A prepared aluminum profile was fed into a specially designed co-extrusion line. In the crosshead die through which the profile passed, a thin layer of hot-melt adhesive was applied to the surface of the powder coating layer, and at the same time, a PVC compound containing a foaming agent was extruded and coated over it. Immediately after passing through the die, micro-foaming occurred inside the PVC layer due to a pressure drop, forming an insulating layer with a thickness of 4 mm, and at the same time, the surface was rapidly cooled by a cooling sizing sleeve, forming a hard skin layer with a thickness of 0.8 mm, thereby successfully manufacturing an integral composite profile.

[0052] [Comparative Example 1] (Conventional adhesive method)

[0053] A separately extruded PVC cover was attached to the same aluminum profile as in Example 1 using an epoxy adhesive.

[0055] [Comparative Example 2] (Powder coating layer member)

[0056] A composite profile was manufactured in the same manner as in Example 1, except that the powder coating process was omitted and a hot-melt adhesive layer was applied directly to the surface of the aluminum profile.

[0058] [Comparative Example 3] (Microfoam layer thickness insufficient)

[0059] A composite profile was manufactured in the same manner as in Example 1, except that the thickness of the microfoamed PVC layer was set to 2 mm.

[0061] [Comparative Example 4] (Exceeding microfoam layer thickness)

[0062] Extrusion was attempted by setting the thickness of the microfoamed PVC layer to 6 mm.

[0064] [Comparative Example 5] (Insufficient hard epidermal layer thickness)

[0065] A composite profile was prepared in the same manner as in Example 1, except that the thickness of the hard epidermal layer was set to 0.3 mm.

[0067] [Comparative Example 6] (Excessive thickness of hard epidermal layer)

[0068] A composite profile was prepared in the same manner as in Example 1, except that the thickness of the hard epidermal layer was set to 1.5 mm.

[0070] [Performance Evaluation]

[0071] The following items were evaluated for the specimens prepared in the above examples and comparative examples, and the results are shown in [Table 1].

[0073] ① Shape precision: Measures the strain relative to the design dimensions of the profile after extrusion.

[0074] ② Thermal transmittance (W / ㎡·K): Measured according to the KS F 2278 test method (lower values ​​indicate better insulation performance).

[0075] ③ Adhesion strength (N / cm): Measure 180-degree peel strength according to the KS M 3726 test method.

[0076] ④ Thermal shock resistance: After repeated exposure to environments of -20℃ and 80℃ for 2 hours each, 100 times, visually observe for the occurrence of delamination and cracking.

[0077] ⑤ Surface Hardness (Pencil): Measure pencil hardness according to the KS M ISO 15184 test method.

[0079] division Shape precision Thermal transmittance (W / ㎡·K) Adhesion strength (N / cm) Thermal shock resistance (100 cycles) Surface hardness (Pencil) Example 1 excellence 1.35 125 No issues 2H Comparative Example 1 excellence 1.82 35 Interfacial delamination 2H Comparative Example 2 excellence 1.36 48 Interfacial delamination occurs 2H Comparative Example 3 excellence 1.95 122 No issues 2H Comparative Example 4 Defect (shape deformation) Unmeasurable Unmeasurable Unmeasurable Unmeasurable Comparative Example 5 excellence 1.38 124 No issues HB Comparative Example 6 excellence 1.61 125 No issues 2H

[0081] [Result Analysis]

[0082] As can be seen in [Table 1] above, Example 1 showed the best performance in all evaluation items.

[0083] Comparative Example 1 (conventional method) shows that the adhesive strength is significantly low and interfacial delamination occurs after the thermal shock test, indicating serious problems with long-term durability. In addition, the thermal insulation performance was also significantly lower compared to Example 1.

[0084] Comparative Example 2 (without a powder coating layer) demonstrates that the adhesive strength is significantly reduced when the powder coating layer is absent, proving that the powder coating layer plays a decisive role in increasing the bonding strength between the aluminum and the adhesive layer.

[0085] Comparative Example 3 (insufficient thickness of the microfoam layer) shows that as the thickness of the microfoam layer decreases to 2 mm, the thermal transmittance deteriorates rapidly to 1.95 W / ㎡·K, demonstrating that a thickness of at least 3 mm is essential to ensure thermal insulation performance.

[0086] In Comparative Example 4 (excessive microfoaming layer thickness), when extrusion was attempted with a thickness of 6 mm, shape deformation occurred due to excessive foaming pressure, making it impossible to produce a normal profile. This clearly demonstrates the critical significance of the process requiring the thickness to be controlled to 5 mm or less.

[0087] Comparative Example 5 (insufficient hard epidermal layer thickness) shows that the surface hardness is very low at the HB grade, making it vulnerable to external scratches. This suggests that a hard layer of at least 0.5 mm is required for surface protection.

[0088] Comparative Example 6 (exceeding the thickness of the hard skin layer) showed that when the hard skin layer was thickened to 1.5 mm, the volume of the non-foamed layer, which lacks thermal insulation function, increased, causing the thermal transmittance to deteriorate to 1.61 W / m²K. This indicates that for optimal thermal insulation performance, the thickness of the hard skin layer should not exceed 1.0 mm. In the same experiment conducted with a hard skin layer thickness of 1.1 mm, the result was 1.48 W / m²K, confirming that the upper limit of the hard skin layer thickness is 1.0 mm.

[0089] In conclusion, it can be experimentally confirmed that each component and its numerical range according to the present invention is an essential configuration organically combined to achieve optimal thermal insulation performance, structural stability, durability, and productivity.

[0091] As described above, the rights of the present invention are not limited to the embodiments described above but are defined by what is stated in the claims, and it is obvious that a person skilled in the art may make various modifications and adaptations within the scope of the rights stated in the claims. Explanation of the symbols

[0093] 1 : Aluminum profile 1a : Dovetail groove 2 : Powder coating layer 3: Hot-melt adhesive layer 4: Microfoamed PVC layer 5: Hard epidermis

Claims

Claim 1 An aluminum profile (1) extruded to form a window frame; a powder coating layer (2) formed by applying a polyester-based powder coating to the aluminum profile (1) using an electrostatic coating method to form a uniform coating thickness within the range of 30 to 60 μm, and then curing in a high-temperature curing furnace to fuse together; a heat-melt adhesive layer (3) formed on the powder coating layer and having viscoelastic properties; and a micro-foamed PVC (polyvinyl chloride) layer (4) formed on the heat-melt adhesive layer, wherein microbubbles generated as molten PVC resin in a high-temperature and high-pressure state passes through an extrusion die and the pressure drops rapidly grow into independent bubbles with a size of 10 μm to 50 μm, having a thickness of 3 mm to 5 mm. An aluminum-plastic composite profile characterized by comprising: a hard skin layer (5) having a thickness of 0.5 mm to 1.0 mm, formed by rapidly cooling the micro-foamed PVC layer and solidifying its surface to form a high-density, hard, non-foamed layer; and being integrally molded by a co-extrusion process. Claim 2 An aluminum-plastic composite profile according to claim 1, characterized in that a plurality of dovetail grooves (1a) are machined on the surface of the aluminum profile (1) where the micro-foamed PVC layer is coated. Claim 3 delete Claim 4 delete Claim 5 An aluminum-plastic composite profile according to claim 1, wherein the powder coating layer (2) is formed by curing a polyester-based powder coating. Claim 6 delete

Citation Information

Patent Citations

  • Steel-plastic co-extruded energy-saving profile full coated with hard PVC (polyvinyl chloride)

    CN103758439A

  • Pvc / cpvc composite pipe with metal interlayer and process for making it

    KR1020100100928A

  • Adhesive-free composite material co-extrusion synthetic resin windows

    KR200340251Y1